eFood Hub – cashless online canteen ordering system for APU students & lecturers - Muhammedh, Ahmed Imam Musadique; Padmakumar, Dhason; Shanmugam, Kamalanathan (Journal of Applied Technology and Innovation, 2021)
University Staffs and Students may typically avoid eating their meals due to deadlines and busy schedules, hence implementing a cashless online canteen ordering system will provide them with an alternative method to get their meals without physically being present at the canteen. Asia Pacific University of Innovation & Technology (APU) already has a cashless payment system implemented in-campus, by integrating a food ordering system which utilizes their existing system will enable APU to promote healthier eating habits in- campus and provide stall operators an alternative stream of income. The proposed system’s inspiration was derived from popular food ordering systems such as Grab Food but with the goal of developing it as an internal system. The developed system will complement the existing cashless card system by adding more features and providing users with an enhanced experience. Users can track, order and pay for their meals via the system. Stall Operators can keep track of all their orders, update order status and manage their menu for their dedicated stall within the application.